The Role of HRM in Developing Technology-Based Competencies - Indarta Priyana; Ifa Khoiria Ningrum; Ahmad Rizani (PT. Anagata Sembagi Education, 2025)
Digital transformation requires employees to possess technology-based competencies as a core capability to maintain organizational competitiveness. This study examines the influence of technology-based training and organizational support on employees’ technology-based competence. A quantitative method was employed using Structural Equation Modeling based on Partial Least Square (SEM–PLS) with 150 employees as respondents. The results reveal that technology-based training has a positive and significant effect on technology-based competence, meaning that greater exposure to digital training leads to higher mastery of workplace technology. Furthermore, organizational support also has a positive and significant effect on technology-based competence, demonstrating that policies, facilities, innovative work culture, and leadership support accelerate the internalization of digital skills in the workplace. Collectively, both independent variables explain 68.4% of the variance in technology-based competence. This study highlights the importance of integrating digital training and organizational support within HRM strategies to build adaptive, innovative, and technology-competent human resources in the era of digital transformation.